Oil, crowns and thrones - Boda, Mark J. 1962- (2001)
In this paper attention to literary-lexical and traditio-historical aspects of Zech 3:1-10; 4:1-14 and 6:9-15, challenges the common interpretation of these pericopae. It is argued that rather than advocating priestly intrusions into prophetic or royal arenas, these passages interpret the arrival and instatement of the Zadokite priestly house as heralding the imminent arrival of the royal house while sustaining an enduring role for prophecy.
Keywords: Bibel; Bibel; Bibel; Priester